Pengaruh Psychological Capital Dan Stres Kerja Terhadap Turnover Intention - Haura, Alya Al; Mardhiyah, Ainun (Peneliti.net, 2025)
The millennial generation is one of the workforce positions that continues to increase in number. This generation will change jobs on average twenty times during their lifetime, compared with traditionalists who work for the same employer until they retire. The creation of effective psychological capital will help reduce the level of employee desire to move, as well as decreasing the stress level in employees will reduce the employee's desire to leave the company. This research aims to analyze